Solar volumetric receiver coupled to a parabolic dish: heat transfer and thermal efficiency analysis - García-Ferrero, Judit (2023)
Concentrated Solar Power plants are commonly recognized as one of the most attractive options within car- bon free power generation technologies because their high efficiency and also because implementation of hybridization and/or storage is feasible. In this work a small-scale system focused on distributed production, in the range of kWe (5kWe to 30kWe), is modeled. A parabolic dish collects direct solar power towards a receiver located at its focus. There, the heat transfer fluid increases its temperature for thermal storage or for directly producing electricity at the power block. Thus, this is a crucial component in CSP systems since it greatly influences global efficiency. There is a trade-off in the energy balance within the thermal receiver, since the higher the temperatures it achieves, the higher the radiation losses could be. In this work, a heat transfer analysis for an air volumetric receiver coupled to a parabolic dish is carried out. The solar receiver is modeled under steady-state conditions using a detailed set of equations. The model considers the main losses by convection, conduction and radiation at the glass window and the surrounding insulator. The tem- peratures and heat transfers along the different receiver zones are computed with a built from scratch in-house code programmed in Mathematica®. The thermal efficiency mainly depends on the incoming solar irradiance at the glass window, the receiver geometry and the type of materials considered, as well as on the ambient temperature. It is expected that this model (precise but not too expensive from the computational viewpoint) could help to identify the main bottlenecks, paving the way for optimization when designing solar volumetric receivers in this kind of systems.